THE IMPACT OF ATTITUDES, SELF-EFFICACY, AND SUBJECTIVE NORMS TOWARD Z-GENERATION’S INTENTION TO CHOOSE THE ACCOUNTING MAJOR - Darmasaputra Alan; Saarce Elsye Hatane; Marchelio Eka Cipta Lieantono; Stefanie Stella Sonbay; Yonatan Tri Eka Putra (International Journal of Financial and Investment Studies (IJFIS), 2022)
The purpose of this research is to examine the roles of family, advisor, and teacher as part of the subjective norm toward high school students’ intention to choose an accounting major at the higher education level. The high school students are the Z-generation. Employing partial lease analysis is to predict model parameters and results of several closed survey questions to validate statistical findings with a total of 351 Indonesian high school students as the respondents. These millennials’ intention to choose the accounting major is positively influenced by their attitudes toward the accounting profession; their self-efficacy; and their supporters (the subjective norms). There are three parties as the supporters of these students: parents, advisors, and teachers. The results imply that parents have the highest influence on the students’ decisions to join the accounting major in the university. However, the existence of advisors and teachers raises the students’ self-efficacy which replaces the position of parents’ opinion. This research contributes to planned behavior literature by comparing the roles of parents and teachers, including advisors, toward the students’ behavior. Moreover, the self-confidence of the students in their ability in accounting encourages them to choose the accounting major in their higher education.